A production of activated carbon using local agricultural waste for groundwater treatment in Universiti Malaysia Pahang - Siti Rohaida, Jamaludin (2010)
The production of activated carbon from local agricultural wastes is one of the most environment-friendly solutions by transforming negative-valued to valueable materials. Two different types of activated carbon were use for production activated carbon which is rice husk and sugarcane baggase. These local agricultural wastes will undergo carbonization process by burn at temperature 5 00'c for 2 hour and cooled before washed using sulphuric acid to activate a pore surface for the carbon. These activated carbon are divided to two different particles size whish are powdered and granular to determine an effective activated carbon for groundwater treatment. The size for granular activated carbon is from 2 mm to 3.35 mm and powdered is from 300 p.m to 63 p.m. Activated carbons are tested for porosity, adsorption and define the pore surface using scanning electron microscope (SEM). The testing has been done show that powdered rice husk activated carbon (PAC RH have a porosity percentage highest compare to another type of activated carbon which is 90 %. A different types and particles size of activated carbon is filling into the filter media for filtering raw water purpose. Different retention time are used which are 15,30,45 and 60 minutes to determine an optimum hydraulic retention time (hrt) that needed to treat a groundwater. Base on observation from the testing that has done, an effective hrt is 30 minute because at this contact time, have a highest removal for several parameters that tested such as turbidity, color, heavy metal and total suspended solid. After this optimum hydraulic retention time, 45 and 60 contact time show a decreasing of removal because of an activated carbon is not functioning well after optimum time.